Electrochemical Fabrication and Sensing Application of Multicolored Silver Films. Issue 13 (2nd May 2018) - Li, Na; Yu, Linan; Wei, Pingping; Ji, Junyi; Zhao, Jiupeng; Zhang, Qiao; Li, Yao; Yin, Yadong
Abstract: This study demonstrates an electrochemical method for the deposition of Ag nanoparticles with anisotropic quasi‐flat structures on solid substrates to form thin films with tunable plasmonic bands covering the full visible range (from 450 to 780 nm). By manipulating the electrodeposition conditions (such as the concentration of capping ligands and pulse voltage), the size and aspect ratio of the deposited silver nanostructures can be controlled and subsequently their plasmonic bands can be tuned. Unlike the free colloidal nanoparticles that often aggregate when exposed to poor solvents, the electrodeposited Ag nanostructured films adhere strongly to the substrates, allowing for their convenient use as effective sensors for the rapid detection of various solvents and their mixtures based on refractive indices. This work provides a new and robust pathway for the preparation of supported plasmonic nanostructured films with controllable morphology and desirable optical property and stability. Abstract : Silver nanostructured thin films with tunable plasmonic bands are fabricated by combining the surfactant‐directed colloidal synthesis and electrochemical deposition process. This novel nanostructured film can be used as effective refractive‐index sensors for detecting solvents and their mixtures with a high sensitivity and excellent stability.